Pharyngocutaneous Fistula after Laryngectomy: An Umbrella Systematic Review to Uncover Lacunae in Meta-Analyses - Karthik Nagaraja Rao; Ripudaman Arora; Ambesh Singh; Prajwal Dange; Nitin M. Nagarkar (MDPI AG, 2023)
Objective-The objective of this study was to systematically assess meta-analyses to determine the lacunae in the literature for PCF following laryngectomy. Methods-Bibliometric analysis were carried out on meta-analyses on PCF after total laryngectomy for laryngeal cancer in the PubMed database. Results-Twenty-four meta-analyses were considered eligible and chosen for analysis. Six meta-analyses (25%) focused on the risk factors for PCF in TL. Four meta-analyses (16.6%) focused on the role of the onlay flap. Four meta-analyses (16.6%) focused on the timing of feed initiation. Three meta-analyses (12.5%) focused on using a stapler for pharyngeal closure. Two meta-analyses focused on types of pharyngeal reconstruction. Other meta-analyses analyzed the use of salivary bypass tubes, the method of pharyngeal closure, organ preservation protocols on PCF, primary and secondary TEP, and the effect of non-surgical treatment on PCF. Conclusion-Despite plenty of published meta-analyses, there is a lack of scrutiny on certain critical aspects of PCF.